Internalisasi Revolusi Mental pada Peserta Didik di SMP Darul ’Ulum Lampung Timur - Ahmad Roza (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
This paper mambahas about the internalization of a mental revolution in SMP Darul Ulum East Lampung. This writing is done using qualitative approaches that aim to describe the internalization of a mental revolution. Based on the results of research and discussion in mind that; internalization refers penghayatan, deepening isolation, merger or unification of attitudes, the standard behavior, opinions and so on within the personality. Furthermore, the mental revolution is transforming the ethos, that fundamental change in mentality, a way of thinking, the way it felt and how to trust, all of which are incarnated in the behavior and actions of everyday. This ethos is concerned all aspects of life, ranging from economics, political science, technology, art, religion, and so on. While internalization of the mental revolution is a process deeply about the values of the revolution are mentally running on SMP Darul Ulum East Lampung. The process of internalization is absolutely essential in a mental revolution, for being a part of educational value.